Solid Acid Hydrolysis for Isolation of Cellulose Nanocrystals and Chitin Nanocrystals – A mini review - Frederikus Tunjung Seta; Xingye An; Hongbin Liu (JURNAL SELULOSA, 2021)
Cellulose and chitin are two of the most abundant biopolymer on earth, have been attracted a lot of interest from many researchers, especially related to their nanoparticles form. Recently the method to extract them into nanoscale materials mostly by mineral or liquid acid hydrolysis, such as sulfuric and hydrochloric acid. Despite their high yield production, many disadvantages are produced by their use as a hydrolysis catalyst, such as low thermal stability and are difficult to be functionalized due to the presence of sulfate groups, tendency to be aggregated due to the bare surface charge density, the potential excessive degradation of cellulose; and large amounts of effluent will be produced due to the neutralization stage and corrosion hazards to the equipment and environment. To overcome the drawback of those acids, solid acid can be used to produce cellulose (CNC) and chitin nanocrystals (ChNC). Their ability to recrystallize and recycle makes them more environmentally friendly, furthermore, most of the acid can do esterification on the surface of cellulose and chitin. The purpose of this paper is to provide a critical review of recent progress related to solid acid hydrolysis since they have interesting characterization even some of their attribute is better than the conventional method.